2019
DOI: 10.1111/ggr.12294
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Gallium Isotopic Compositions in Reference Materials

Abstract: The interest in the study of gallium (Ga) stable isotope fractionation in low‐ and high‐temperature environments has increased significantly in the last few years. However, a unified reference material (RM) is still lacking for the Ga isotope research community, which hinders interlaboratory comparison between different groups. Consequently, certification of Ga isotopic reference materials for interlaboratory comparison is of high priority. In this study, Ga isotope ratio data for ten geological RMs including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Data precisions of better than 0.06‰ (2SD), with a variation in δ 71 Ga values of up to 1.83‰ across different industrial and natural materials were achieved, opening the way for Ga isotopic approaches in various research studies. However, studies using the different purification methods reported inconsistent δ 71 Ga values for certain reference materials (Feng et al., 2019; Kato et al., 2017, Wimpenny et al., 2020; Yuan et al., 2016; Zhang et al., 2016), requiring further study of technique reliability. We performed an international calibration and comparison of δ 71 Ga values for set reference materials, with results indicating that δ 71 Ga values, relative to both the NIST SRM 994 and IPGP‐Ga standard (Feng et al., 2019; Kato et al., 2017, Yuan et al., 2016; Zhang et al., 2016), of our newly purchased reference materials JG‐2, BHVO‐2, and BCR‐2 were consistent with those reported previously by other laboratories (Figures 11 and 12, Table S9).…”
Section: The Isotopic Geochemistry Of Gamentioning
confidence: 99%
See 3 more Smart Citations
“…Data precisions of better than 0.06‰ (2SD), with a variation in δ 71 Ga values of up to 1.83‰ across different industrial and natural materials were achieved, opening the way for Ga isotopic approaches in various research studies. However, studies using the different purification methods reported inconsistent δ 71 Ga values for certain reference materials (Feng et al., 2019; Kato et al., 2017, Wimpenny et al., 2020; Yuan et al., 2016; Zhang et al., 2016), requiring further study of technique reliability. We performed an international calibration and comparison of δ 71 Ga values for set reference materials, with results indicating that δ 71 Ga values, relative to both the NIST SRM 994 and IPGP‐Ga standard (Feng et al., 2019; Kato et al., 2017, Yuan et al., 2016; Zhang et al., 2016), of our newly purchased reference materials JG‐2, BHVO‐2, and BCR‐2 were consistent with those reported previously by other laboratories (Figures 11 and 12, Table S9).…”
Section: The Isotopic Geochemistry Of Gamentioning
confidence: 99%
“…Yuan et al (2016) studied the adsorption of Ga on surfaces of calcite and goethite minerals, and found significant Ga isotopic fractionation (up to 1.3‰) during Ga adsorption (Yuan et al, 2018), foreshadowing the potential application of Ga isotopes in tracing and characterizing surface biogeochemical processes. Previous studies have also reported that industrially produced Ga materials are significantly enriched in the heavy isotope relative to geological materials, foretelling the usefulness of Ga isotopes for distinguishing natural from anthropogenic sources (Feng et al, 2019;Kato et al, 2017;Yuan et al, 2016;Zhang et al, 2016). It is thus safe to conclude that Ga isotopes are likely to provide additional clues concerning yet-underconstrained Al behavior and its biogeochemical cycle, and shed new light on other biogeochemical processes in which Ga is involved.…”
Section: The Isotopic Geochemistry Of Gamentioning
confidence: 99%
See 2 more Smart Citations
“…Gallium isotopic compositions of several geological RMs have been analysed by Feng et al . (2019). Geng et al .…”
Section: Journal No Of Papersmentioning
confidence: 99%